2012
DOI: 10.1155/2012/634914
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Cultured H9 Human Embryonic Stem Cells with Thyroid Stimulating Hormone Does Not Lead to Formation of Thyroid-Like Cells

Abstract: The sodium-iodine symporter (NIS) is expressed on the cell membrane of many thyroid cancer cells, and is responsible for the radioactive iodine accumulation. However, treatment of anaplastic thyroid cancer is ineffective due to the low expression of NIS on cell membranes of these tumor cells. Human embryonic stem cells (ESCs) provide a potential vehicle to study the mechanisms of NIS expression regulation during differentiation. Human ESCs were maintained on feeder-independent culture conditions. RT-qPCR and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…To verify this in our cell cultures, we stained H9 and H14 hESC, HT1080 fibrosarcoma cells, and IMR90 primary fibroblasts for heterochromatin marker H3K9me3. We also differentiated our H9 and H14 hESC towards the endodermal lineage using activin A and bFGF as previously described [ 15 ], to directly compare these cells to the differentiated lineages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify this in our cell cultures, we stained H9 and H14 hESC, HT1080 fibrosarcoma cells, and IMR90 primary fibroblasts for heterochromatin marker H3K9me3. We also differentiated our H9 and H14 hESC towards the endodermal lineage using activin A and bFGF as previously described [ 15 ], to directly compare these cells to the differentiated lineages.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the cells were maintained in mTeSR1 medium at 5% CO 2 and 37 °C for two days with medium changed each day. Starting from day 3, cells in culture were maintained in differentiation media: DMEM/F12 (Stemcell Technologies, Vancouver, BC, Canada) supplemented with 5% KSR (knockout serum replacement) (Invitrogen, Grand Island, NY, USA), 100 ng/mL Activin A (Stemcell Technologies), 4 ng/mL bFGF as was described previously in [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…34,39-41 D'Amour et al 42 reported similar results using human cells, observing that in the presence of FGF-2 highdose activin A induced a massive differentiation of ESCs into transcription factor SOX-17 + /Foxa2 + definitive endodermal cells ( Figure 4 and Table 1). Interestingly, Onyshchenko et al 43 used two methods in order to differentiate human ESCs in thyroid follicular cells: (i) an one-step protocol that aims at a direct differentiation through TSH stimulation by avoiding the intermediate endoderm formation and (ii) a two-step protocol with an intermediate passage in endodermal cells, which foresees the TSH stimulation in combination with activin A and FGF-2. In both cases, we were unable to obtain an efficient generation of differentiated cells that express specific thyroid markers.…”
Section: Normal Thyroid Stem Cellsmentioning
confidence: 99%